Flip the tweet – the two-sided coin of entrepreneurial empathy and its ambiguous influence on new product development - Kurz, Konstantin; Bock, Carolin; Hanschur, Leonard (Journal of Business Venturing, 2024)
Is empathy a uniformly good thing for entrepreneurs? Contrasting the hitherto predominantly positive view advocated by the extant entrepreneurship literature, we develop a novel model of entrepreneurial empathy's mechanisms and suggest a ‘too-much-of-a-good-thing’ perspective. We empirically confirm this model using a dataset of 4425 real entrepreneurs, where we find that empathy influences entrepreneurial new product development as an essential entrepreneurial activity in an inverted U-shaped pattern. We further show that empathy's negative effects are particularly detrimental for very anxious entrepreneurs. These findings provide strong evidence for considering entrepreneurial empathy an important but highly ambiguous success factor.